A simplified preoperative risk assessment tool as a predictor of complications in the surgical management of forearm fractures - Congiusta, Dominick (J Clin Orthop Trauma, 2020)
PURPOSE: Frailty is a well-known predictor of adverse postoperative outcomes and is often considered in the preoperative planning stage of surgery. In recent years, the modified frailty index (mFI), a novel metric used to quantify frailty, has become increasingly used in the orthopedic literature as a risk assessment tool. In this study, we analyze the utility of the mFI in predicting unplanned repeat operations and morbidity in the surgical treatment forearm fractures. METHODS: We used the American College of Surgeons National Surgical Quality Improvement Program 2006–2014 dataset to identify patients undergoing open fixation of forearm fractures. The mFI was calculated based on 5 possible comorbid conditions. Demographic and predictor variables were analyzed for associations with each outcome. In order to assess frailty in both the general and elderly population, two analyses were completed: one for the entire population and one for a population of age 65 or older. The primary outcome of interest was unplanned repeat operation. Secondary outcomes included discharge destination and major post-operative complications. Chi square and logistic regression analyses were used to identify associations. RESULTS: A total of 4641 patients were included in our final analysis. There was a higher prevalence of females and patients between the ages of 61 and 80 compared to other age groups. An mFI score ≥2 was a positively associated with unplanned repeat operation in the general population. An mFI score ≥2 was also positively associated with a discharge destination other than home and major post-operative complications. In the elderly population, mFI ≥2 was similarly associated with a discharge destination other than the patient’s home. CONCLUSIONS: Patients undergoing open treatment of forearm fractures were at an increased likelihood of having an unplanned repeat operation and having major complications as frailty score increased, demonstrating that the mFI may be clinically applicable risk assessment tool for these patients.